Tensions and Transitions in the Muslim World: By Louay Safi (Lanham, MD: University Press of America, 2003. 231 pages.) (American Journal of Islam and Society, 2005)
This book belongs to the genre of studies attempting to extend and broadenMuslim channels of communication to “western” academic and intellectualcircles in general, and to their American counterparts in particular. It startsfrom the conventional apologetic premise that Islam is misunderstood and,in many instances, mystified both by unrepresentative scholarly works onthe one hand, and the dynamics of Muslim history and actions on the other.Marked differences between the historical, social, and political experiencesof Muslims and Europeans, as reflected in different modes of organizationand discourse, have put serious impediments in the way of mutual understandingacross the cultural divide separating the two worlds.One reflection of such distrust is manifested in the indifference shownby American scholars and statesmen toward what Safi designates as“Islamic reformists” and their forward-looking agenda. Despite the latter’sambitions to advance a pluralist and democratic society in consonance withthe modern world, the former continue to dismiss such claims as both“opportunistic” and insincere. These perceptions, according to the author,are driven by a strong sense of skepticism about the commensurability ofIslamic values with modern western ideals as well as by vested Americangeostrategic interests.Safi challenges such attitudes by emphasizing the importance and vitalsignificance of Islamic reform, which he defines as the “middle ground andthe moral synthesis between the nationalist-secularist and the moral-Islamist forces” at the heart of the unsettling tensions that inform sociopoliticaltransformations in the Arab and Islamic worlds (p. xii). Reform ofthis kind should be able to appropriate the universal elements of the historicalMuslim experience in order to transcend the political and cultural institutionsof classical and contemporary Muslim societies, and to bring abouta creative synthesis of Islam and modernity (p. xi). Safi’s main contention ...